Cardiovascular Intervention in Neonates Using an Umbilical Vein Approach - Ying-Tzu Ju; Yu-Jen Wei; Yung-Chieh Lin; Min-Ling Hsieh; Jing-Ming Wu; Jieh-Neng Wang (Children, 2021)
Cardiovascular catheterization has been applied in infant treatment for several decades. To date, considerable research attention has been paid to cardiovascular catheterization in small neonates. However, peripheral vascular routes of catheterization are possible obstacles for interventionists. Umbilical vein catheterization has been reported as a route for neonates, although few attempts have been made to investigate this approach. This study aimed to retrospectively review cardiovascular intervention using the umbilical vein approach as applied to infants admitted to a tertiary center from 2017 to 2020. Details including the perinatal variables, indication diagnoses, and procedure devices were collected. The enrollment included a total of 16 cases representing 17 intervention events, with infants born at a gestation age of 22–39 weeks and body weight ranging from 478 to 3685 g at the time of the procedure. The postnatal age ranged from 1 to 27 days. The catheter sizes ranged from 4 to 11 Fr. Indications included being admitted for patent ductus arteriosus occlusion (n = 15), balloon pulmonary valvuloplasty (n = 3), balloon atrial septostomy (BAS) (n = 3), pulmonary valve (PV) perforation (n = 1), and two interventions for catheter placement for continuous venovenous hemofiltration. The success rate for cardiovascular catheterization was 88.2% (15/17). There were two patients for which cannulation failed due to ductus venosus closure: one intraabdominal hemorrhage complication during continuous venovenous hemofiltration (CVVH), and one cardiac catheterization failure of PV perforation due to failure to insert the guiding catheter into the right ventricular outflow tract. Based on these findings, we conclude that cardiac catheterization and the placement of a large-sized catheter through an umbilical vein in a small infant represents a safe and time-saving method when catheterization is required.